Interrelationships between autobiographical memory specificity, executive functions and rumination in depression - Kızılöz, Burcu Kaya. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Depression is associated with reduced specificity of autobiographical memories (Williams & Broadbent, 1986), a phenomenon defined as overgeneral memory. It has been suggested that rumination, impairments in executive functions and functional avoidance underlie OGM (Williams et al., 2007). The present study has three main goals: 1) to examine whether different executive functions are affected by depression differently 2) to clarify the nature of the relationship between rumination and executive functioning deficits and 3) to examine the effects of cue type on memory specificity in depression. To reach these aims, participants were divided into two groups according to their Beck Depression Inventory (BDI) scores as high (n = 45) and low (n = 51) BDI participants. They then completed the Ruminative Responses Scale and EF tasks for shifting, updating and inhibition and reported important and word-cued ABMs. Results showed that word-cued memories resulted in more OGMs than important memories for all participants, regardless of BDI scores. Only shifting predicted specificity of autobiographical memories for word-cued memories but not for important memories. Consistent with earlier claims, certain EF deficits were related to OGM for word-cued memories, but no evidence of a link between rumination and OGMs was found.
Keywords: Depression, Mental.; Autobiographical memory.